Tasapainoilua : kuusi reittià Himalajalle. - Gill, Simryn; Heikkilä, Jussi; Jaukkuri, Maaretta; Rasmussen, Hans Hamid; Roberts, Liisa; Wilson Lloyd, Ann; Xu, Bing (Helsinki : KIASMA Museum of Contemporary Art, 2000)
The idea for an exhibition based on a trip by a multinational group of artists to the Himalayan mountains in Nepal has been under discussion at Kiasma since as long age as 1995. The original idea came from the artist Jussi Heikkilä. This was further developed together with him into the form in which its first phase, i.e. the trip to the Himalayas, took place in October 1999. Those who embarked on the trip, apart from Heikkilä, were Xu Bing, Honoré d'O, Simryn Gill, Hans Hamid Rasmussen and Liisa Roberts.
biog., ind. tent. gr. tent. p. 76-80
Engels & Fins
Delicate Balance : six routes to the Himalayas, KIASMA (Museum of Contemporary Art) Helsinki, 22.6. - 10.9.2000
boek
Keywords: Xu Bing; d'O, Honoré; Gill, Simryn; Heikkilä, Jussi; Rasmussen, Hans Hamid; Roberts, Liisa; Himalaya; Nepal